Emotional health: A study with school managers in Santa Catarina - Valgas , Bruna Piacentini Stupp; Ramadam, Amanda Oliveira (Seven Editora, 2024)
This study aims to analyze the situations and demands experienced by school managers of public schools, who work in the Regional Coordination of Tubarão (CRE) of Santa Catarina (SC), in order to contribute to the improvement of their emotional health. Seeking to identify the responsibilities of the role and its importance for improving the quality of school education in their community. This is an applied research, with an exploratory approach, through bibliographic and documentary survey, with semi-structured interviews conducted with managers of the CRE of Tubarão/SC. In view of the information gathered by this research, it was possible to understand that the school manager assumes a significant role in the school context and that his performance has a considerable impact on the improvement, or not, of the teaching offered, as well as on the promotion of student learning and in all aspects of its development and in the formation of an educational environment favorable to teaching. The discussions presented demonstrate the complexity of the aspects that involve the administration of educational spaces in a democratic and participatory way. It is concluded that the managers participating in this study, even in the face of the challenges of their attributions and responsibilities placed in the role of school manager, do not measure efforts to carry out a work of excellence, which takes place through the constant search for improvement in the teaching offered and in the interaction with the entire school community with the objective of improving education. It was concluded that, necessarily, the function requires managers to be able to deal with pressure, strategic knowledge, and conflict resolution, but it is understood that the lack of professional support affects their emotional health and personal life. This study is extremely relevant, because an unmotivated manager will hardly be able to motivate his team. And actions should be thought of by the coordination in order to minimize the manager’s work overload for a better quality in the educational process. DOI:https://doi.org/10.56238/sevened2024.009-002